The actual and anticipated effects of restrictions on flavoured electronic nicotine delivery systems: a scoping review - Christopher J. Cadham; Alex C. Liber; Luz María Sánchez-Romero; Mona Issabakhsh; Kenneth E. Warner; Rafael Meza; David T. Levy (BMC, 2022)
Abstract Objective To synthesize the outcomes of policy evaluations of flavoured electronic nicotine delivery systems (ENDS) restrictions. Data sources PubMed, Scopus, Embase and Web of Science before May 3, 2022. Study selection Studies that report sales, behaviour, or compliance outcomes related to implemented or hypothetical ENDS flavour restrictions. Data extraction Restriction details, whether implemented or hypothetical, whether additional products were restricted, jurisdictional level, study locations, and outcomes classified by sales, behaviour, and compliance. Data synthesis We included 30 studies. Of those, 26 were conducted exclusively in the US, two in India, and two surveyed respondents in multiple countries, including the US. Twenty-one evaluated implemented restrictions, while nine considered hypothetical restrictions. Five studies evaluated product sales, 17 evaluated behaviour, and 10 evaluated compliance, with two studies reporting multiple outcomes. Two studies reported an increase and one a reduction in cigarette sales following restrictions, while three reported reductions in ENDS sales. Behavioural studies presented a mixed view of the impacts of regulations on ENDS and cigarette use. However, the use of disparate outcomes limits the comparability of studies. Studies of hypothetical restrictions suggest decreased ENDS use, increased cigarette use, and increased use of illicit markets. Studies of compliance with flavoured product restrictions that included ENDS found that 6-39% of stores sold restricted flavoured products post-restrictions. Online stores remain a potential source of restricted products. Conclusion Our findings highlight the need for additional research on the impacts of ENDS restrictions. Research should further evaluate the impact of restrictions on youth and adult use of nicotine and tobacco products in addition to the effects of restrictions in countries beyond the US to enable a robust consideration of the harm-benefit trade-off of restrictions.